Maqashid Sharia Analysis of Muhammadiyah’s Fund Withdrawal from Bank Syariah Indonesia: Toward Achieving the SDGs - Nadhif Rais Al-Mufti; Muthoifin; Kiran Nawaz (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: The primary objective is to assess whether the institutional financial practices of BSI align with the ethical, social, developmental, and sustainability goals emphasized by Muhammadiyah, particularly in empowering micro, small, and medium enterprises (MSMEs), promoting inclusive economic growth, and advancing the collective welfare of the ummah in line with the Sustainable Development Goals (SDGs). Theoretical framework: This framework allows for a dynamic and integrative analysis of Islamic legal and economic reasoning within modern institutional and macroeconomic structures, aligning with global development paradigms like the SDGs. Literature review: The literature review addresses three interrelated domains: (1) the evolving relationship between Islamic organizations and financial institutions, (2) the development of contemporary Maqashid Syariah frameworks, and (3) the role of institutional trust and ethical alignment in Islamic finance. Methods: This research adopts a qualitative-descriptive method using library research as the primary approach. Data was collected from academic literature, official documents, media reports, and primary sources from Muhammadiyah and BSI. Results: Findings indicate that Muhammadiyah’s withdrawal was driven by dissatisfaction with BSI’s prioritization of corporate-scale financing over inclusive support for MSMEs. Although the financial loss to BSI was relatively small (about 4.4% of third-party funds), the symbolic impact was substantial, signaling a critical shift in institutional alignment and ethical accountability. The move reflects Muhammadiyah’s commitment to financial justice, economic inclusivity, and alignment with SDG-related objectives. Implications: The study's implications are twofold: (1) for Islamic financial governance, it calls for deeper alignment with maqashid-oriented principles that support SDG implementation; and (2) for Islamic civil society actors, it emphasizes the importance of principled fund management that advances justice, development, and trust in financial ecosystems. Novelty: The novelty of this research lies in the application of Jasser Auda’s systems theory of Maqashid Syariah not to product evaluation, but to institutional decision-making and inter-organizational dynamics—a critical yet underexplored dimension of Islamic economic thought with direct relevance to sustainable development discourses.